Water and sanitation policies in Argentina: the challenge of universalizing services - Cáceres, Verónica L. (2014)
This article is aimed at contributing to the reflection and debate on the water and sanitation policies in Argentina. For this purpose, regulatory and institutional aspects are discussed regarding services management in the country. The paper also includes a characterization of the five stages of such policies that have marked the progress of the sector. Finally, the main challenges faced by the sector are mentioned as a conclusion.